Functional Connectivity Underlying Symptoms in Preschool Boys With Autism: A Resting-State Functional Magnetic Resonance Imaging Study - Lan, Zhihong; Xu, Shoujun; Yu, Xiangrong; Yu, Zhenjie; Li, Meng; Chen, Feng; Liu, Yu; Wang, Tianyue; Wu, Yunfan; Gan, Yungen; Jiang, Guihua (Frontiers in Neuroscience, 2022)
Background: Single-sex children have been regarded as one of the best subjects to understand the abnormal development patterns of autism spectrum disorders (ASDs). However, the functional connectivity (FC) behind their symptoms is still unknown. Methods: Based on FC analysis, the acquired resting-state functional magnetic resonance imaging (rs-fMRI) data sets, including 86 boys with ASD and 54 normal controls (NC), were used to detect the neural synchronous activity between brain regions. Pearson correlation analysis was used to evaluate the relationship between the abnormal FC value and clinical features. Results: Individuals with ASD showed enhanced FC between the right calcarine and the right lingual gyrus. The right medial orbital frontal cortex also showed increased FC with bilateral inferior temporal gyrus (two-tailed, voxel-level p < 0.001, gaussian random field (GRF) correction, cluster-level p < 0.05). We did not find a correlation between the abnormal FC value and clinical scales. Conclusion: Our study reveals a possible relationship between atypical visual attention and poor learning ability in subjects with ASD, and delayed social language development may be a secondary symptom to ASD.